The Effect of Ship Coefficients on the Efficiency Gain f Propeller-Vane System - Setyo Leksono; IKAP Utama; MA Djoni; WD Aryawan (IPTEK The Journal of Engineering, 2015)
This paper discusses a correlation between non dimensional parameter of the ship (L/B,B/T, wake fraction, ratio between induced and advance velocity, thrust loading coefficient) and energy gain by applying vane-turbine in the propeller slipstream. The data based on the basis of statistical data (numerical) and model testing. The correlation data can be calculated by quantifying the contribution of causal variables to a targeted effect variable directly and indirectly through other variables and this would be examined by Path analysis. By using this coefficient, it is possible to demonstrate which variable has the main contribution on the efficiency gain. The Data analysis of Microsoft Office Excel software is used to approach the calculation. It is found that L/B and CT affected indirectly the efficiency gain of vane-turbine